IFRS and Secrecy: Assessing Accounting Value Relevance Across Africa. (5th November 2015) - Hillier, David; Hodgson, Allan; Ngole, Shaban
Abstract: We examine the value relevance of accounting across several African countries and test whether IFRS improved the value association of earnings and equity book values. We report a stronger valuation association between accounting and stock prices in African countries classified as having a secrecy culture. This increases after IFRS and more so for earnings. On the other hand, IFRS induced a stronger increase in the book value coefficient in the less secretive and more developed South African market. We surmise that the more conceptual focus of IFRS induced an increased demand for higher‐quality accounting professionals, which had a filtering‐down effect of improving quality information flow and breaking down the secrecy culture. Our research highlights the diverse impacts of IFRS and the role of culture, asset markets and accounting professionalism, in driving the relevance of accounting components across Africa.